A case report of synchronous ameloblastoma and odontogenic keratocyst of the mandible. (12th November 2020) - Belknap, A.N.; Vidican, C.B.; Cohen, D.M.; Bhattacharyya, I.; Islam, M.N.; Gohel, A.
Abstract: We present a report of bilateral mandibular radiolucent lesions that were diagnosed as synchronous ameloblastoma and odontogenic keratocyst (OKC) in a 75‐year‐old female patient. To the best of our knowledge, the simultaneous occurrence of ameloblastoma and OKC of the jaws, as contralateral lesions, has not been previously reported.